2012
DOI: 10.1038/cdd.2012.3
|View full text |Cite
|
Sign up to set email alerts
|

HDAC5 is required for maintenance of pericentric heterochromatin, and controls cell-cycle progression and survival of human cancer cells

Abstract: Histone deacetylases (HDACs) form a family of enzymes, which have fundamental roles in the epigenetic regulation of gene expression and contribute to the growth, differentiation, and apoptosis of cancer cells. In this study, we further investigated the biological function of HDAC5 in cancer cells. We found HDAC5 is associated with actively replicating pericentric heterochromatin during late S phase. We demonstrated that specific depletion of HDAC5 by RNA interference resulted in profound changes in the heteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 38 publications
3
63
0
3
Order By: Relevance
“…18 Myoferlin siRNA sequences are the same as above. ONTARGETplus nontargeting pool (Thermo Fisher-Dharmacon, Whaltham, MA) was used as irrelevant siRNA control.…”
Section: Small Interfering Rna Transfectionmentioning
confidence: 99%
“…18 Myoferlin siRNA sequences are the same as above. ONTARGETplus nontargeting pool (Thermo Fisher-Dharmacon, Whaltham, MA) was used as irrelevant siRNA control.…”
Section: Small Interfering Rna Transfectionmentioning
confidence: 99%
“…Autophagy induction upon HDAC5 depletion/inhibition was attributed to induction of ROS, as it was prevented by ROS scavenger N-acetyl-L-cysteine (NAC) (Figures 2i and j). With published electron microscopy analysis showing presence of mitochondria engulfed in autophagosomes, 9 we hypothesized that ROS-producing mitochondria were selectively degraded by a specific autophagic process called mitophagy. 16 Parkin, p62 and LC3 proteins in the mitochondria-enriched fraction were more abundant in HDAC5-depleted cells (Figure 2k), suggesting a higher mitophagy flux in these cells.…”
Section: Panc-1mentioning
confidence: 99%
“…Interestingly, iron dysregulation modulated the accumulation of ROS and cell death upon LMK235 (Figures 3f − h) or SAHA treatment (Supplementary Figures S4B − D). Finally, since we previuously reported that HDAC5 depletion potentiates the effect of chemotherapeutic agents such as cisplatin 9 and there are indications in the literature that iron can influence cisplatin toxicity, 17,18 we examined the role of iron in cisplatin-induced cell death upon HDAC5 depletion. Apoptosis of HDAC5-depleted cells co-treated with cisplatin was blocked after addition of NAC, suggesting that cisplatin-induced apoptosis upon HDAC5 depletion is associated with oxidative stress (Figure 3i).…”
Section: Panc-1mentioning
confidence: 99%
See 2 more Smart Citations